Social Issues in the Zoroastian Religion (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, we can learn about one of the biggest signs of the custom of people's funeral in the southern and bordering regions of Uzbekistan, and about its characteristics. At the same time, it is thought about the emergence of the first city-states in Central Asia, in particular, Ancient Bactria and Margyona.